Targeted delivery of C/EBPα -saRNA by pancreatic ductal adenocarcinoma-specific RNA aptamers inhibits tumor growth in vivo - Yoon,S; Huang,KW; Reebye,V; Mintz,P; Tien,YW; Lai,HS; Sætrom,P; Reccia,I; Swiderski,P; Armstrong,B; Jozwiak,A; Spalding,D; et al. (Molecular Therapy, 2016)
The 5-year survival rate for pancreatic ductal adenocarcinoma (PDAC) remains dismal despite current chemotherapeutic agents and inhibitors of molecular targets. As the incidence of PDAC constantly increases, more effective multidrug approaches must be made. Here, we report a novel method of delivering antitumorigenic therapy in PDAC by upregulating the transcriptional factor CCAAT/enhancer-binding protein-α (C/EBPα), recognized for its antiproliferative effects. Small activating RNA (saRNA) duplexes designed to increase C/EBPα expression were linked onto PDAC-specific 2′-Fluropyrimidine RNA aptamers (2′F-RNA) - P19 and P1 for construction of a cell type–specific delivery vehicle. Both P19- and P1-C/EBPα-saRNA conjugates increased expression of C/EBPα and significantly suppressed cell proliferation. Tail vein injection of the saRNA/aptamer conjugates in PANC-1 and in gemcitabine-resistant AsPC-1 mouse-xenografts led to reduced tumor size with no observed toxicity. To exploit the specificity of the P19/P1 aptamers for PDAC cells, we also assessed if conjugation with Cy3 would allow it to be used as a diagnostic tool on archival human pancreatic duodenectomy tissue sections. Scoring pattern from 72 patients suggested a positive correlation between high fluorescent signal in the high mortality patient groups. We propose a novel aptamer-based strategy for delivery of targeted molecular therapy in advanced PDAC where current modalities fail.